A doença como ponto de mutação :os processos de significação em mulheres portadores de lúpus eritematoso sistêmico - Araujo, Adriana Dias (2004)
Systemic lupus erythematous (SLE) is a chronic and auto-immune disease that can affect several systems of one´s body, including the nervous system, causing several clinical evidences, which can put in risk the person´s life. Although the illness could manifest itself at any age or sex, studies indicate higher incidence among women. Its etiology points to the combination of genetic, hormonal and environmental factors. Due to the disease´s complexity, it is evident that it affects all the person´s life as a whole and not only its organic dimension. It is believed that the signification attributed to all the process of sickening influences its treatment, as well as the person´s capacity to cope with the difficulties and implicit profits involved in the process.In this study, eight women who were affected by SLE were interviewed, with the aim of examining carefully the processes of signification as well as the generation of meanings which permeate these women´s sickening processes. The analysis of their speeches evidences distinct forms of giving meaning to the process, regardless of the time of the diagnosis. The fact that the disease is incurable was shocking to all the participants, and it demanded changes in their lives, in order to detain a relative control of their condition. The majority of the participants were able to deal with these modifications, since strategies have been created to face the difficulties and thus to preserve their social life, without damaging their health. However, some of the participants did not obtain strenght to cope with the disease, eventually developing a depressive state. It is observed that not only SLE has innumerable ways of manifestation, but the experience of the illness is very subjective and dynamic. There are also several ways of expressing this experience, according to the implications in the social, cultural and economic context where the participants are inserted. This ratifies the necessity of a interdisciplinary approach to embrace SLE complexity. (310 words, 1.610 characters)